The museum of intangible things - Wunder, Wendy (Razorbill, 2014)
Best friends Hannah and Zoe, seventeen, leave their down-and-out New Jersey town and drive west chasing storms, making new friends, and seeking the intangibles--audacity, insouciance, happiness--that their lives have lacked.